Challenges & opportunities of grocery retail during pandemic: An insight into the case of Malaysia - Phang Ing @ Grace; Zaiton Osman; Izyanti Awang Razli; Lim Tze-Yin; Iwao Kato (Sarawak Research Society, 2022)
pandemic has hit the world with surprise, and the impacts on socio-economic aspects are believed to linger longer even after it's ended. Building upon stress theory and social learning theory, this study aims to synthesize the changes in consumer patterns and behaviors as well as the challenges and opportunities grocery retailers are experiencing during the pandemic emergency in Malaysia at the end of the year 2020. Interviews were conducted in order to obtain the insights shared by the grocery retailers, and content analysis and qualitative aided software such as Quirkos were utilized. The findings suggested a few opportunities related to consumer patterns and behavior changes throughout the Pandemic. Besides, the challenges of merchandise and store management were addressed in the current study.